Low back ache in working women of reproductive age group in an urban area - Nupur Nandi; Banasree Bhadra (Barpeta Obstetrics and Gynaecological Society, 2018)
Background - Back pain is a common complaint and is acknowledged as an important socioeconomic and health problem. Low back ache (LBA) not only leads to poor quality of life for individuals all over the world but also leads to decreased productivity. Objective - This study was taken up with the aim to establish the prevalence of LBA in women of reproductive age group. In addition, correlation of LBA with overweight, reproductive factors, like age at marriage, marriage duration, past pregnancy, number of children or abortions, and posture during working were evaluated. Materials and Methods - It was one year prospective study on working women in reproductive age group (18-49 years) who presented in the out patient department of Obstetrics and Gynaecology. They were interviewed through questionnaire after obtaining an informed consent. Statistical analysis of data was done by proportions and tests of significance. Results - The prevalence of LBA was 57.7%. The symptoms of LBA were more among women who were married after 30 years of age (62%), had more ≥2 deliveries (60.6%) and had ≥2 abortions (78.8%). Prevalence of LBA was more among women with BMI ≥30 and who worked in sitting posture for > 3 hours. Conclusion - Prevalence of LBA in working women in reproductive age group is high. There is correlation between LBA and age at marriage, past pregnancy (including previous deliveries and abortions), obesity and posture while working. Thus attention must be paid to weight control, posture while working and time duration at work place.